Empowering youth: developing spiritual and intellectual enhancement in youth - U Tun Aung, Maulana Akbar Shah (2019)
In this era of information and technology engaging around us, knowledge has been made the essential foundation to build a modern and dynamic generation of a country. Even our holy book of guidance, the Quran, has repeatedly called believers to continue to seek knowledge as a way to transform ourselves as vicegerents of the Almighty. Chapter 45, verse 13 of the Quran, emphasized that knowledge is the perfect medium for us to reflect and understand the attributes of Allah through his creations. Thus, as the generation of this modernized era, we should consistently seek the opportunity to increase our knowledge in various aspects, be it spiritually or otherwise. To this, it cannot be denied that most of our knowledge is attained through a formal educational institution, specifically schools. Such an institution provides convenient learning space, ambiance, and facilities to mould the students into a figure that is well equipped with concrete facts and information, as well as the fundamental communication skills needed. The assistance of schools in shaping these students give out great importance since they are considered to be future leaders. Focus and emphasis should be channelled to improvise the characteristics of the youth of today, as we know by nurturing them to become successful leaders of tomorrow should be carried out at a young age. Through this study, we get to witness first-hand the situation that the students nowadays are going through at school. The prerequisites to a good education, which are the school facilities and the school environment must be taken care of, to establish a quality learning process. However, the standard of youth in our society is not up to the mark as anticipated. The background of this study is to highlight the decay of morality, lack of discipline, deterioration of healthcare, and its system in schools, weakening the mental strength of our youth, which is rampant in our community. Hence, the objective of this paper is to observe the five main attributes of the students, discipline, physical strength, spiritual power, mental quality, and behaviour change, which are the primary key to determine whether our youths are on the right track in configuring leaders of tomorrow. The methodology applied in this research is quantitative, for that, questionnaires will be prepared, interviews with school children from targeted primary and secondary schools in Gombak area will be conducted, analysis of interviews’ reports will be conducted consequently, and finally, the publication of the polished paper is planned at the end.